2014
DOI: 10.3892/ijo.2014.2322
|View full text |Cite
|
Sign up to set email alerts
|

miR-7 inhibits glioblastoma growth by simultaneously interfering with the PI3K/ATK and Raf/MEK/ERK pathways

Abstract: Abstract. Epidermal growth factor receptor (EGFR) signaling regulates glioblastoma cell proliferation, survival, migration and invasion and plays a key role in tumor progression. We show that microRNA-7 (miR-7) is a common regulator of the phosphoinositide-3-kinase (PI3K)/ATK and Raf/ mitogen-activated protein kinase kinase (MEK)/extracellular signal-regulated kinase (ERK) pathways, both of which are launched by EGFR through its two direct targets, the transcription factors PI3K and Raf-1, respectively. Enforc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(90 citation statements)
references
References 39 publications
(42 reference statements)
2
86
0
2
Order By: Relevance
“…However, the molecular mechanisms underlying these observations remain unclear. Recent reports indicate miRNAs as an important factor, and the abnormal expression of some miRNAs are involved in GDNF-mediated signaling pathways [31-34]. We tested the hypothesis that GDNF promotes glioma cell proliferation and migration by modulating the expression of specific miRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the molecular mechanisms underlying these observations remain unclear. Recent reports indicate miRNAs as an important factor, and the abnormal expression of some miRNAs are involved in GDNF-mediated signaling pathways [31-34]. We tested the hypothesis that GDNF promotes glioma cell proliferation and migration by modulating the expression of specific miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown abnormal miRNA expression in malignant glioma [28, 29], and these miRNAs can be useful biomarkers [30]. Moreover, some are involved in signaling pathways activated by GDNF, such as c-Jun N terminal kinase (JNK), extracellular signal-regulated kinase 1/2 (ERK-1/2), and p38 MAPK signaling pathways, to promote malignant glioma metastasis and invasive growth [31-34]. Therefore, we hypothesized that high GDNF expression promotes glioma cell proliferation and migration by modulating the expression of specific miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Microarrays showed that miR-7 inhibits multiple oncogenic pathways to suppress HER2-mediated breast cancer and reverse trastuzumab resistance in vitro. [54][55][56] Moreover, miR-7 is reported to inhibit cell growth and invasion in pancreatic cancer cells, and could sensitize non-small cell lung cancer cells to paclitaxel. 57,58 A study in cervical cancer found that miR-7 inhibited the metastasis and invasion of cervical cancer by targeting focal adhesion kinase (FAK) at the transcriptional and translational levels.…”
Section: Roles Of Circrnas In the Oncogenesis And The Malignant Behavmentioning
confidence: 99%
“…Also, miR-7 is expressed abundantly in human pancreas and endocrine cells and has a specific role in endocrine cell differentiation and function [10] . It has been demonstrated that miR-7 is a tumor suppressor in breast, lung and ovarian cancers, and glioblastoma, mainly focusing on its relationship with EGFR [11][12][13][14][15] . Accumulating evidence shows that miR-7 can simultaneously target a variety of mRNAs involved in diverse signaling pathways in different tumors.…”
Section: Introductionmentioning
confidence: 99%